1995
DOI: 10.1287/mnsc.41.11.1720
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Determinants of Service Quality and Performance: Evidence from the Banking Industry

Abstract: This paper focuses on an important new service management strategy: the operations capabilities-service quality-performance (C-SQ-P) triad. In order to understand what generic operations capabilities influence the strategic behavior of high performing service firms, we explore three related questions: What generic operations capabilities are among the strategic determinants of service quality? Does service quality affect market performance? How is market conduct related to the C-SQ-P triad? These questions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(222 citation statements)
references
References 29 publications
8
213
0
1
Order By: Relevance
“…Consistent with existing literature, more knowledgeable employees better deliver services that match customer needs (Roth and Jackson 1995), help reduce organizational uncertainty, decrease process variability, and advance a firm's ability to adjust to new conditions. Furthermore, when customers coproduce knowledge, they feel like part of the service and closer to the organization.…”
Section: Deploymentsupporting
confidence: 54%
“…Consistent with existing literature, more knowledgeable employees better deliver services that match customer needs (Roth and Jackson 1995), help reduce organizational uncertainty, decrease process variability, and advance a firm's ability to adjust to new conditions. Furthermore, when customers coproduce knowledge, they feel like part of the service and closer to the organization.…”
Section: Deploymentsupporting
confidence: 54%
“…Others consist more of routines and processes to generate and diffuse knowledge and learning within the organization to increase effi ciencies, improve products, and reduce costs. This categorization is similar to "inside-out" and "outside-in" capabilities (Moorman & Slotegraaf, 1999), internal and external learning (e.g., Bierly & Chakrabarti, 1996;Roth & Jackson, 1995), fan-out and fan-in capabilities (Hart & Sharma, 2004), and external and internal integrative capabilities (Verona, 1999) discussed in the literature.…”
Section: The Research Contextmentioning
confidence: 82%
“…Apte and Vepsalainen (1993) examined the tradeoff between using "high tech" versus "high touch" channels and argued that the former is effective for cost reduction and the latter is more effective for relationship building. Roth and Jackson III (1995) found a negative correlation between total factor productivity and service quality, which underscores the importance of cost-benefit tradeoffs in service design. Menor et al (2001) showed that operations agility, which is defined as the ability to excel simultaneously on operations capabilities of quality, delivery, flexibility and cost, is as vital for retail banks' performance as it is for manufacturing firms.…”
Section: Online Service In Financial Servicesmentioning
confidence: 82%